Expression of (TTF-1), CK-7 and CK-20 Immunohistochemical Marker in Neoplastic and Non-neoplastic Endometrium. - AL-Atrooshi, Sazan A.; Hameedi, Ameer D.; Zaboon, Zainab A. (Journal of the Faculty of Medicine Baghdad, 2015)
Background: Thyroid transcription factor-1 (TTF-1) is a protein that is well known to be expressed immunohistochemically in normal and neoplastic thyroid and pulmonary tissues. However; increasing studies have showed its expression in normal tissues and tumors of other organs including endometrium. These facts are important to be considered in the use of this marker in the differential diagnosis of carcinoma of unknown origin and make it important to use it as a part of a panel of immunohistochemical stains. In this setting Cytokeratin 7 and 20(CK-7&CK-20) are important since they have different coordinate expression profile in different organs and tumors.Obejectives: This study is designed to assess expression of TTF-1, CK-7 and CK-20 in neoplastic and nonneoplastic endometrium.Patients and Methods: Thirty six cases have been studied including 23 case of endometrial carcinoma and 13 cases of non-neoplastic endometrium including cases of irregular secretory endometrium, simple hyperplasia, complex hyperplasia, complex atypical hyperplasia, and atrophic endometrium.The study performed in the Baghdad medical city from May 2013 to December 2013Results: Two cases out of 23 cases of endometrial carcinoma (8.7%) showed expression of TTF-1 and none of the non-neoplastic endometrial cases showed any expression. Twenty one (91.3%) of 23 cases of endometrial carcinoma and all non-neoplastic endometrial cases showed expression for cytokeratin 7 with different scores.Neither neoplastic nor non-neoplastic endometrium showed expression for cytokeratin 20.Conclusion:We concluded that although TTF-1 regarded as a marker for thyroid and pulmonary tissues (and tumors); other tumors “including cases of endometrial carcinomas can showed TTF-1 expression. CK7+ve/CK20-ve profile of endometrial carcinoma is important to consider in assessment of carcinoma of unknown origin especially if combined with TTF-1.